2013
DOI: 10.1021/cm4025028
|View full text |Cite
|
Sign up to set email alerts
|

Design of Functional Materials Based on Liquid Crystalline Droplets

Abstract: This brief perspective focuses on recent advances in the design of functional soft materials that are based on confinement of low molecular weight liquid crystals (LCs) within micrometer-sized droplets. While the ordering of LCs within micrometer-sized domains has been explored extensively in polymer-dispersed LC materials, recent studies performed with LC domains with precisely defined size and interfacial chemistry have unmasked observations of confinement-induced ordering of LCs that do not follow previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
178
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 146 publications
(190 citation statements)
references
References 100 publications
10
178
0
2
Order By: Relevance
“…[10] When nematic LCs are confined to water-dispersed microdroplets, the interfacial interactions of the LC set the orientation of the LCs at the droplet surface (i.e., surface anchoring). [11, 12-14] To accommodate the surface anchoring conditions, the LC within the interior of the droplet assumes a variety of configurations that involve elastic strain of the LC (e.g., splay, bend, etc.) [14-18] and topological defects (localized regions where the LC effectively melts).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] When nematic LCs are confined to water-dispersed microdroplets, the interfacial interactions of the LC set the orientation of the LCs at the droplet surface (i.e., surface anchoring). [11, 12-14] To accommodate the surface anchoring conditions, the LC within the interior of the droplet assumes a variety of configurations that involve elastic strain of the LC (e.g., splay, bend, etc.) [14-18] and topological defects (localized regions where the LC effectively melts).…”
Section: Introductionmentioning
confidence: 99%
“…[11, 12-14] To accommodate the surface anchoring conditions, the LC within the interior of the droplet assumes a variety of configurations that involve elastic strain of the LC (e.g., splay, bend, etc.) [14-18] and topological defects (localized regions where the LC effectively melts). [15, 16, 19, 20, 21] At equilibrium, the ordering of the LC within the microdroplets reflects minimization of the combined contributions of surface anchoring, bulk elastic deformations and topological defects to the free energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments and simulations have also shown that the defects that arise in LC droplets can be used to localize individual nanoparticles or pairs of nanoparticles with considerable precision (16, 17). More generally, droplets offer an effective, yet simple means for confining LCs, thereby controlling the balance of interfacial and elastic contributions to the free energy and the response of LCs to external cues (18,19). Depending on surface anchoring, LC droplets can exhibit two primary morphologies (20).…”
mentioning
confidence: 99%
“…Liquid crystalline droplets of polymeric mesogens dispersed in continuous polymer phases have been investigated previously, but recently these droplets have demonstrated remarkable orientational sensitivity to interfacial interactions. 31 Our spherical nematic droplets have a radial structure (Figure 3) where the director field ïżœ is orthogonal to the droplet surface, or in other words, the GO basal plane is tangential to the surface (Figure 3d top) -the easy direction of orientation imposed by surface tension forces. Figure 3b shows the orientation of the slow axis measured with the birefringence mode and Figure 3c the orientation of high transmittance direction measured using the diattenuation mode.…”
mentioning
confidence: 99%